Study guide to accompany Money, banking, and the economy - Beckman, Steven; Mayer, Thomas, 1927-; Dimmen, Janet Wolcutt (New York : W. W. Norton, 1996)
This book contains five parts: Finance: institutions and theory; The supply of money; Money, National income, and the price level; Monetary policy; and The international monetary system.
Keywords: Economics; Banks; United States; Money; Money -- United States -- Problems, exercises, etc; Banks and banking -- United States -- Problems, exercises, etc; Monetary policy -- United States -- Problems, exercises, etc